PKM PENGUATAN PROFIL PELAJAR PANCASILA DENGAN MEDIA ECOPRINT BERBASIS TEKNIK POUNDING - Sirait, Syahriani; Putri Lidiana Permata Sari; Anim, Anim; Wati, Herni Wati Julianingsih; Amelia Putri; Silvia, Siska Silvia (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
In the Pancasila Student Profile, creativity is defined as a student's ability to modify and create something that is original, meaningful, useful and has a positive impact. In developing student creativity, PKM was held to strengthen the profile of Pancasila students using ecoprint media based on the pounding technique. Dyeing using the ecoprint method based on the pounding technique is an environmentally friendly method, which uses natural ingredients to create patterns on the fabric. Ecoprint based on the pounding technique is a method of dyeing fabric that uses leaves, flowers and other parts of plants that are transferred to the surface of the fabric through a beating process. The aim of this community service is to develop student creativity, because creativity is one of the dimensions of the Pancasila student profile. The production process involves selecting tote bag materials from natural fabrics, such as calico, which are more effective in absorbing colors from plant materials. After that, fresh leaves and flowers are placed on the cloth, then beating and drying techniques are carried out to transfer the natural patterns of the plants to the surface of the cloth. In this study, various types of leaves were tested to determine the variation in pattern and color resistance produced. The results of the ecoprint making training which was carried out as a form of developing the creativity of students at SD Negeri 010246 Banjar.